The effectiveness of treffinger’s learning model in increasing the creativity and mathematics achievement of gifted students - Kana Hidayati; Ni Kadek Swari Nandini; Mazlini Adnan (Jurnal Riset Pendidikan Matematika, 2021)
This study aims to describe the difference in creativity and mathematics achievement between gifted students who were taught by Treffinger's learning and those who thought by the expository learning in trigonometry material. This study is a quasi-experiment using a pretest-posttest group design with a population of all gifted students in class X of a State Senior High School in Bali, Indonesia. The sample was established randomly. Observation sheets, pre-test, post-test, and student creativity questionnaires were used, all of which have been validated. The data were analyzed descriptively and inferentially with the paired sample t-test to test the mean difference of the pre-test and post-test data. The results show that the average creativity of students in the experimental class is significantly higher by 9.46 points than that of the control class. In terms of mathematics learning achievement, the average gain score in the experimental class increased significantly by 58.365 points. It can be concluded that Treffinger’s learning is effective in increasing creativity and mathematics achievement of gifted students in trigonometry material.